2023
DOI: 10.3390/membranes13080691
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation between Biodegradable Magnesium Metal GBR Membrane and Bovine Graft with or without Hyaluronate

Marko Blašković,
Dorotea Blašković,
David Botond Hangyasi
et al.

Abstract: Bone substitutes and barrier membranes are widely used in dental regeneration procedures. New materials are constantly being developed to provide the most optimal surgical outcomes. One of these developments is the addition of hyaluronate (HA) to the bovine bone graft, which has beneficial wound healing and handling properties. However, an acidic environment that is potentially produced by the HA is known to increase the degradation of magnesium metal. The aim of this study was to evaluate the potential risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 54 publications
0
0
0
Order By: Relevance
“…Wound dehiscence was previously reported in an in vivo study using the membrane [16]. However, in this instance, and in concurrence with the published cases [24][25][26][27], there were no clinical observations associated with the release of hydrogen gas.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Wound dehiscence was previously reported in an in vivo study using the membrane [16]. However, in this instance, and in concurrence with the published cases [24][25][26][27], there were no clinical observations associated with the release of hydrogen gas.…”
Section: Discussionsupporting
confidence: 85%
“…As it degrades, it releases magnesium ions, which are naturally prevalent within the body and are present in almost every cell [21]. Its initial mechanical strength provides a rigid three-dimensional volumetric maintenance to stabilize the underlying bone graft during the critical healing period, yet reabsorbs in the subsequent months following implantation in a complete and predictable way [14,16,[22][23][24][25][26][27]. The membrane has undergone substantial preclinical research [14,16], and since its CE approval, its clinical performance has been reported in several case studies [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Even though the patient's own bone is considered to be the gold standard grafting material, different synthetic or naturally-derived biomaterials are used to simplify the grafting procedure [12]. Especially the bovine derived xenograft granules in combination with hyaluronate provide better handling at the grafted site due to the sticky consistency [13]. This also leads to faster cells proliferation and vascularization compared to the xenograft granules alone [7], [8].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies showed that hyaluronic acid biofunctionalization of the bovine bone substitute cerabone ® caused an increased activity of human osteoblasts, thus indicating the ability to accelerate and improve bone regeneration [24,27]. Based on the findings of the in vitro studies, the innovative bone graft substitute was tested in in vivo models.…”
Section: Biofunctionalization Of Bone Substitute Materialsmentioning
confidence: 99%
“…Given the properties of cerabone ® plus, including osteoconductivity and volume stability, this relatively new bovine bone substitute material enables time-saving and efficient defect filling and easy defect contouring [30,31]. After hydration, cerabone ® plus is sticky and malleable, thereby minimizing displacement of single granules during application [24,27]. It can therefore be applied for horizontal and vertical augmentation [31], peri-implant defects [30], socket preservation and sinus lifts.…”
Section: Clinical Applicationsmentioning
confidence: 99%